DAMPAK LOAN TO DEPOSITE RATIO TERHADAP PROFITABILITAS (Studi Kasus Pada PT. Bank XYZ Banten) - Ellyta Muchtar (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2016)
The function of the bank as a financial intermediary which means collecting funds from the public and channel them back to the community in the form of loans. Sources of funds used to finance the loan portfolio is derived from third party funds, the amount of loan interest income will be followed by the amount of interest expense paid to the customer. Objective Research to determine whether there is significant influence and how much influence the Loan to Deposit Ratio to the Bank's profitability as measured by Return on Assets. The method used is a causal research conducted quantitatively with the data available on the website perusahaan.Data analyzed with quantitative approach, namely the correlation analysis and multiple linear regression analysis were processed by SPSS16.0 software. Samples are one of the commercial banks in Banten, West Java which financial data is taken from the financial statements that have been published through the website of the bank concerned. The results obtained by the analysis and data processing value LDR variable correlation with significance 0.182 meaning> than 5% so that it can be concluded between the LDR there is no connection with the bank's profitability. Interpretation of the correlation coefficient value, value - 0524 showed the level of the trade-offs between LDR with bank profitability. Rated R Square 0275 means indicates that LDR capabilities in explaining the level of bank profitability  amounted to 27.5% The results of this study showed that the increase in bank lending to the public is not matched by an increase in profitability of the acquired bank. Key words : Loan To Deposite Ratio (LDR), Profitabilitas, ROA